Ethnobotany and preliminary bioactivity investigation on hepatoprotective medicinal plants from the Mouhoun Region of Burkina Faso - Jotham Yhi-pênê N'DO; André TIBIRI; Ernest Nogma SOMBIE; Tata Kadiatou TRAORE; Noufou OUEDRAOGO; Adama HILOU; Pierre Innocent GUISSOU; Odile Germaine NACOULMA (International Journal of Phytomedicine, 2018)
An ethnobotanical survey of medicinal plants used to treat hepatitis in the Mouhoun region of Burkina Faso was undertaken. The extracts of the most quoted species were then evaluated for their phytochemistry and their antioxidant activity The anti-radical activity (by the method of the discoloration of the ABTS cation radical) and that of the antioxidant (by the method of the reduction of the iron ion, FRAP) were evaluated. Then the phenolic content of the aqueous extracts was determined and a correlation was studied between these two parameters. The antioxidant tests showed that the plants counted have a good antioxidant power. The three most active extracts are those of the trunk and root bark of Pseudocedrela kostchyi, and the trunk bark of Sterculia setigera. The extract of the bark of the trunk of Sterculia setigera showed the highest total tannin and phenolic content, while that of the leaves of Piliostigma reticulatum showed the highest content of flavonoids. The analyses showed that there is a relationship between the total phenolic contents and the antioxidant capacities of all the extracts (R2 = 0.82). The extracts of the trunk and root barks of Pseudocedrela kostchyi, and that of the trunk bark of Sterculia setigera showed the best antioxidant properties. They could be good candidates for the search for liver protective molecules